Pengaruh Tingkat Pendidikan Orang Tua dan Jalur Masuk Terhadap Prestasi Belajar Mahasiswa Akuntansi (Studi pada Mahasiswa Jurusan Akuntansi Universitas Brawijaya Malang) - Asti Tyas Handayani; Unti Ludigdo (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study purpose to determine the influence of education’s parent and the university recruitment’s way on learning achievement. This study used a different test in testing the two-way anova analysis. Based on the results of education’s parent variables or the university recruitment’s way testing, both variables have a positive and significant impact on accounting learning achievement. Education’s parent is measured by the latest education taken by the parents. The university recruitment’s way were measured by the college admission when new student admissions. Learning achievement is proxied by Grade Point Advantage. The indication, the parental education as high as child's learning achievement. The people intelligence level affected to the results of study, where each university recruitment’s way indicates of the intelligence. Keywords: education’s parent, the university recruitment’s way, learning achievement